Shaft and base resistance of non-displacement piles in sand. (March 2017) - Han, Fei; Salgado, Rodrigo; Prezzi, Monica; Lim, Jeehee
Abstract: This paper presents the results of three-dimensional, finite element analyses performed with an advanced, two-surface-plasticity, constitutive sand model to investigate the response of non-displacement piles to axial loading. The analysis domain is carefully meshed such that the formation and evolution of shear bands next to the pile shaft and near the pile base can be properly captured. Analyses considering various soil profiles and pile geometries show that the mobilized lateral earth pressure coefficient K along the pile shaft increases with increasing relative density and decreasing initial confining stress. The ultimate unit base resistance is independent of pile diameter, increasing with increasing relative density and increasing initial confining stress at the pile base. Based on the analysis results, design equations are proposed to estimate the limit shaft resistance and ultimate base resistance of non-displacement piles in sandy soil. In proposing these relationships, the pile slenderness ratio is considered. The effect of layer proximity to the base of the pile or pile base embedment in a layer is also considered.